2018
DOI: 10.14507/epaa.26.3530
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between test preparation and state test performance: Evidence from the Measure of Effective Teaching (MET) project

Abstract: The passage of the NCLB Act enhanced accountability policies in the United States, and standardized testing became prevalent as a policy tool to ensure accountability in K-12 education. Given the high stakes of state administered accountability tests, more school teachers have adopted test-preparation strategies to ensure satisfactory student performance on state tests. However, it remains unclear as to whether and how test preparation relates to students’ state test performance. In this study, by drawing on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…More recent studies confirm previous research findings of an association of modest score gains with test preparation for the ACT (Schiel & Valiga, 2014a;Schiel & Valiga, 2014b;Schiel & Valiga, 2014c;Appelrouth, Zabrucky, & Moore, 2015;Buchman, Condron, & Roscigno, 2010, Moss, Chippendale, Mershon, & Carney, 2012Li & Xiong, 2018;Lane et. al , 2009).…”
Section: Draft Manuscript For Ncme 2019 Dissemination April 6 2019supporting
confidence: 85%
“…More recent studies confirm previous research findings of an association of modest score gains with test preparation for the ACT (Schiel & Valiga, 2014a;Schiel & Valiga, 2014b;Schiel & Valiga, 2014c;Appelrouth, Zabrucky, & Moore, 2015;Buchman, Condron, & Roscigno, 2010, Moss, Chippendale, Mershon, & Carney, 2012Li & Xiong, 2018;Lane et. al , 2009).…”
Section: Draft Manuscript For Ncme 2019 Dissemination April 6 2019supporting
confidence: 85%
“…In other words, this means that teachers are inclined to adopt traditional teaching and pursue test-oriented teaching not only in grade 8 but also in grades 5, 6, and 7. However, in a study by Li and Xiong (2018), it was revealed that the time spent on test preparation by students in class negatively impacted their performance in high-stakes testing. In conclusion, it can be asserted that the impacts of high-stakes testing on the learning-teaching process will prevent the development of students in the cognitive, affective, and psychomotor domains and the realization of education policies regarding students' acquisition of 21st-century skills.…”
Section: Discussionmentioning
confidence: 99%
“…for proper allocation to be addressed. Because it is not uncommon for schools to spend a tremendous amount of time and money on testing preparation [31]. Marassa [32] advocated incorporating skills into the curriculum with adequate financial support.…”
Section: Careful Budget Planningmentioning
confidence: 99%